Perancangan Benovation Creative Hub dengan Pendekatan Arsitektur Eco-Tech dan Adaptasi Kehidupan Sosial Baru Pasca Pandemi Covid-19 - Retno Fitri Astuti; Risna Yuwinda (Prosiding Sains dan Teknologi, 2022)
The diversity of local creative products in West Java contributes significantly to national economic growth. Seeing this potential, the West Java Government made special Regional Regulations and has a program to build creative hubs in every Regency/City. However, unlike in other big cities which already have many creative hubs, Bekasi Regency still lacks facilities like this. Many Small and Medium Industry (IKM) products in Bekasi Regency have not yet obtained certification and many creative millennials have business ideas but do not have room for production, capital and product development. In addition, since the 2019 coronavirus disease, creative economic growth in Bekasi Regency has also decreased. By using data collection methods in the form of observation, literature and comparative studies, the design of the Benovation Creative Hub aims to facilitate in supporting creative economic activities in the Bekasi Regency area. This design will combine an eco-tech architectural design concept approach which includes adapting the concept of "new normal". That in fact lately we are still in the new normal situation of the Covid-19 pandemic. Of course, we hope that this condition will end quickly, but choosing to remain consistent in carrying out a "new normal" lifestyle is one of the efforts and good habits to create a healthier environment and life through building design adjustments that facilitate the needs and comfort to carry out this style. that life. Keywords: Creative Hub, Bekasi Regency, Eco-tech Architecture, New Normal